Association Between Passive Smoking and Menstrual Discomfort: A Cross-Sectional Study of 2,571 Non-smoking Chinese Nurses - Xiao, Shi-qi; Xing, Lin-lin; Wu, Qi-jun; Xia, Tian-hui; Fu, Tong-tong; Guo, Ying; Yu, Xin-ying; Sun, Xiang-hong; Feng, Hui-ling; Gai, Li; Xu, Yi-wei; Xia, Chun-ling; et al. (Frontiers in Public Health, 2022)
Introduction: Menstrual discomfort affects women’s quality of life, which is an important public health issue. Evidence confirming the link between passive smoking and menstrual discomfort is limited. Therefore, the aim of this study is to investigate the aforementioned topic on the basis of a cross-sectional study of 2571 nonsmoking Chinese nurses. Methods: Demographic information and passive smoking were assessed using a self-administered questionnaire. Menstrual discomfort was characterized as dysmenorrhea, illness or weakness, bed rest, and restlessness during menstruation, which were assessed using a modified version of the Cornell Medical Index-Health Questionnaire. Multivariate-adjusted odds ratio (OR) and 95% confidence intervals (CIs) were estimated using the logistic regression model. Results: A total of 1195 nurses (46.48%) were exposed to passive smoking. Compared with non-passive smoking nurses, passive smoking nurses were more likely to have menstrual discomfort symptoms (72.38% vs. 64.39%), especially symptoms of dysmenorrhea (49.54% vs. 42.08%), illnesses or weakness (48.28% vs. 42.08%), and restlessness during menstruation (53.05% vs. 46.22%). Exposure to passive smoking was significantly associated with menstrual discomfort (OR=1.41, 95%CI: 1.19–1.67), especially symptoms of dysmenorrhea (OR=1.32, 95%CI: 1.13–1.56), illness or weakness (OR=1.24, 95%CI: 1.06–1.46), and restlessness (OR=1.26, 95%CI: 1.08–1.48) during menstruation. The subgroup analyses, stratified by age, children, and marital status, agreed with the main findings. Conclusions: Exposure to passive smoking was related to symptoms of dysmenorrhea and menstrual discomfort.